Risk assessment of aflatoxin B1 in herbal medicines and plant food supplements marketed in Malaysia through margin of exposure approach - Ab Dullah, Siti Soleha (2022)
Aflatoxin B1 (AFB1) is a mycotoxin produced by several species of Aspergillus fungi that can induce liver cancer in animals and humans upon ingestion of AFB1-contaminated food. This study aims to perform the risk assessment of AFB1 in herbal medicines and plant food supplements (PFS) marketed in Malaysia through the margin of exposure (MOE) approach. A total of 31 herbal medicines and PFS samples were purchased through online platforms and over-the-counter using targeted sampling method. Samples extracted with 70% methanol were subjected to immunoaffinity column filtration and quantified using ELISA assay. Next, the MOE was calculated using the benchmark dose lower level of 10 (BMDL10) of 63.46 ng/kg bw/day derived from the animal carcinogenicity data, and the estimated daily intake (EDI) among Malaysian adults ranged from 0.006 to 10.456 ng/kg bw/day. MOE below 10, 000 indicate the urgency for risk management actions. The estimated percentage of liver cancer attributable to AFB1 exposure was calculated by dividing the target population risk per year per 100,000 population by the agestandardised incidence rate for liver cancer. AFB1 was detected in 80.6% of samples analysed at a level ranging from 0.275 to 13.941 μg/kg. The calculated MOE ranged from 6.07 to 10227.35. In total, 24 (96%) out of 25 positive samples had MOE below 10,000. The risk of liver cancer ranged from 0 to 0.261 cancers per 100,000 population per year and the estimated percentage of liver cancer incidence ranged from 0.002% to 4.149%. This study found a moderate risk of liver cancer in Malaysian populations due to AFB1 from herbal medication and PFS, emphasising the need for risk management measures.